2020
DOI: 10.3390/safety6020021
|View full text |Cite
|
Sign up to set email alerts
|

Using a Neural Network Analysis to Assess Stressors in the Farming Community

Abstract: In the 1980s and 1990s, with decreasing numbers of full-time farmers and adverse economic conditions, chronic stress was common in farmers, and remains so today. A neural network was implemented to conduct an in-depth analysis of stress risk factors. Two Colorado farm samples (1992–1997) were combined (n = 1501) and divided into training and test samples. The outcome, stress, was measured using seven stress-related items from the Center for Epidemiologic Studies-Depression Scale. The initial model contained 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The prevalence of chronic diseases appears to be more common among farm entrepreneurs than among the working population in Finland ( Perkiö-Mäkelä et al, 2016 ). Similarly, Beseler and Stallones (2020) found that health, the economic situation, and disease related to pesticides were key elements increasing stress among Colorado farmers. In Finland, a nationally representative population sample (n = 5,834) measured the work ability index among salaried workers, entrepreneurs with and without personnel, and farmers: the score for farmers was lower (37.9) than for the other groups and the whole sample on average (40.0) ( Saarni et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of chronic diseases appears to be more common among farm entrepreneurs than among the working population in Finland ( Perkiö-Mäkelä et al, 2016 ). Similarly, Beseler and Stallones (2020) found that health, the economic situation, and disease related to pesticides were key elements increasing stress among Colorado farmers. In Finland, a nationally representative population sample (n = 5,834) measured the work ability index among salaried workers, entrepreneurs with and without personnel, and farmers: the score for farmers was lower (37.9) than for the other groups and the whole sample on average (40.0) ( Saarni et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%
“…In our surveillance data, 49.8% of principal operators worked 75% or more on the farm/ranch but in second and third operators combined only 16% worked more than 75% on the farm/ranch. Younger farmers are more likely to work off the farm (USDA, 2017), although the added time pressure might be expected to increase the risk of injury by increasing stress (Beseler & Stallones, 2020). Older farmers may have greater assistance from family members as they transition to retirement.…”
Section: Discussionmentioning
confidence: 99%